Associação de imagens a um sistema musical interativo - Luiz Gustavo Vianna Batista (2011)
The development of an interactive music system accompanied by images, purpose of this work, offered a unique opportunity to the manipulation of algorithms, ideas and concepts related to the use of audio and video processing in live performances, which resulted in an experiment called Teste nº1. The achievement of a compact and efficient system, to be used mainly by a sole musician and his/her personal computer, was accompanied by a series of personal decisions, succinctly dealt with in the Introduction, facing the delicate issue of the association of languages, the conceptualization of interactive music systems, and the choice of the softwares to be used.Two chapters deal with the two main processes in this experiment: "data sensing/acquisition, and its eventual processing. An Intermezzo, simultaneously splitting and integrating both chapters, comes into play, discussing the pragmatism inherent to the notions of time and music-writing, traces of the western music heritage unavoidable in this work.